2018
DOI: 10.1590/1678-4685-gmb-2017-0165
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia risk variant rs600753 is linked with dyslexia-specific differential allelic expression of DYX1C1

Abstract: An increasing number of genetic variants involved in dyslexia development were discovered during the last years, yet little is known about the molecular functional mechanisms of these SNPs. In this study we investigated whether dyslexia candidate SNPs have a direct, disease-specific effect on local expression levels of the assumed target gene by using a differential allelic expression assay. In total, 12 SNPs previously associated with dyslexia and related phenotypes were suitable for analysis. Transcripts cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…[ 8 ] At present, the Dyx1c1 −/− mouse is an ideal model of dyslexia and is widely used to study the pathogenesis of dyslexia‐related deficits. [ 27 , 28 , 29 , 30 , 31 ] Knockdown of Dyx1c1 in rat embryos leads to the loss of the ability of the neocortical neurons to migrate to the proper position, indicating that Dyx1c1 is essential for nervous system development. [ 32 ] Further studies showed that Dyx1c1 knockdown in the forebrain of the mouse resulted in impairment of learning and memory, indicating that Dyx1c1 is critical for the development of the learning and memory part of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] At present, the Dyx1c1 −/− mouse is an ideal model of dyslexia and is widely used to study the pathogenesis of dyslexia‐related deficits. [ 27 , 28 , 29 , 30 , 31 ] Knockdown of Dyx1c1 in rat embryos leads to the loss of the ability of the neocortical neurons to migrate to the proper position, indicating that Dyx1c1 is essential for nervous system development. [ 32 ] Further studies showed that Dyx1c1 knockdown in the forebrain of the mouse resulted in impairment of learning and memory, indicating that Dyx1c1 is critical for the development of the learning and memory part of the brain.…”
Section: Introductionmentioning
confidence: 99%